MASIHKAH PELATIHAN DAN PENGEMBANGAN SDM MEMPENGARUHI KINERJA STUDI PADA TARUNA SIAGA BENCANA (TAGANA) KABUPATEN SUBANG - Silvia, Iyang Cucu; Firmansyah, Yayan (Eko dan Bisnis: Riau Economic and Business Review, 2019)
This study aims to determine: (1) the effect of training on performance of Taruna Siaga Bencana (Tagana), (2) the effect of human resources development on performance of Taruna Siaga Bencana (Tagana), (3) and the effect of Training and Development of Human Resources on Performance of Taruna Siaga Bencana (Tagana). The method used in this study was descriptive and verification. The data were collected by questionnaire and interview techniques. Respondents in this study amounted to 78 people who were members of Taruna Siaga Bencana (Tagana). The results of this study indicate that: (1) Training has a positive and significant effect on the performance of Tagana (9.63%). (2) Development of human resources has a positive and significant effect on the performance of Tagana (20.5%). (3) Training and development Human resources have a positive and significant effect on performance of Taruna Siaga Bencana (Tagana) with a coefficient of 47.7%, while the remaining 52.3% is influenced by other variables which are not examined in this study. Job training and Development Human resources are very beneficial for Taruna Siaga Bencana (Tagana) Kab. Subang to make them be ready in the task of disaster management stages. Therefore, training and development programs for human resources need to be improved and carried out sustainably and has a clear implementation